Feasibility and Preliminary Efficacy of an Internet Support Group for Parents of a Child with Neurofibromatosis Type 1: a Pilot Study. Issue 3 (7th November 2016) - Martin, S.; Roderick, M. C.; Lockridge, R.; Toledo‐Tamula, M. A.; Baldwin, A.; Knight, P.; Wolters, P.
Abstract: This pilot study investigated the feasibility and preliminary efficacy of an Internet Support Group (ISG) for parents of children with NF1. Eligible parents were recruited by email and completed baseline questionnaires assessing social support, self‐efficacy, depression, and anxiety. The ISG involved eight weekly 90‐min chat sessions and a discussion forum open 24 h/day for 8 weeks. Follow‐up measures were completed immediately post‐intervention and 3 months later. Parents from 33 families (29 mothers, 4 fathers) completed baseline measures. Over half of parents (52 %) rated their child's disease severity as mild, 33 % moderate, and 15 % severe. Among 21 parents who completed post‐intervention measures, ratings of perceived emotional ( p = .0008) and informational ( p = .0003) support increased. There were no significant changes in self‐efficacy, depression, or anxiety ( p s > .05). The mean satisfaction rating was moderately high (7.6/10; range 4–10). Some parents commented that the chat sessions were at inconvenient times, which may have limited participation. Preliminary evidence in this small sample of parents suggests that ISGs may be a feasible and potentially efficacious method of providing support to parents of children with NF1. Having multiple weekly chat sessions held at various days and times may improve accessibility and participation. Clinicians are encouraged to help parents access online support resources.